DEVELOPMENT OF A SYSTEM FOR FORECASTING THE AMOUNT OF DODOL SALES USING THE WEIGHTED MOVING AVERAGE METHOD - Rindi Sindia; Iqbal Kamil Siregar; MHD Ihsan (STMIK Royal, 2022)
Abstract: Dodol is a type of sweet food made from palm sugar that is processed with various flavors and takes a long time to complete. Dodol is also a type of food in great demand by the public due to its elasticity and characteristic taste. The manufacture and sale of this lunkhead are produced by UD. Maya Sari is located in the Kisaran area, especially in the Tanjung Alam Village, Dusun 3, Asahan Regency. Forecasting (forecasting) is thinking about a quantity, for example. The number of product requests for the future. Difficulties in forecasting inventory are often experienced by businesses, including UD. Maya Sari is difficult to predict the supply of lunkhead for the future. The research conducted by this author aims to build a system that can predict sales for the future in increasing a business's income. The system is well designed with PHP and UML for system workflow. Keywords: Dodol sales; Forecasting System; Weighted Moving Average Method Abstrak: Dodol merupakan salah satu jenis makanan manis berbahan dasar gula aren yang diolah dengan berbagai rasa dan membutuhkan waktu yang lama dalam pembuatannya. Dodol juga merupakan jenis makanan yang banyak diminati oleh masyarakat karena kekenyalan dan rasa yang khas. Pembuatan dan penjualan dodol ini diproduksi oleh UD. Maya Sari yang berada di kawasan Kisaran khususnya di Desa Tanjung Alam Dusun 3 Kabupaten Asahan. Peramalan (forecasting) adalah memikirkan kuantitas. Misalnya Jumlah permintaan produk untuk masa yang akan datang. Kesulitan dalam peramalan persediaan seringkali dialami oleh para pelaku usaha, termasuk UD. Maya Sari sulit memprediksi pasokan dodol untuk masa depan. Penelitian dilakukan. Hal ini bertujuan untuk membangun sebuah sistem yang dapat memprediksi penjualan dimasa yang akan datang guna meningkatkan pendapatan usaha. Sistem ini dirancang dengan baik dengan PHP dan UML untuk alur kerja sistem. Kata Kunci : Metode Weighted Moving Average; Penjualan dodol; Sistem Peramalan